Future of French and European fisheries after Brexit : management of shared fish stocks between the European Union and the United Kingdom - Fanton, Etienne (HAL CCSD, 2024)
At a time when the planet is undergoing its sixth mass extinction, the regulation of fishery, a protein source accessible globally, is essential for the sustainable management of this resource. We have thus assessed the significance of this industry on a worldwide, European, and French scale. Following an overview of the construction and evolution of European policies aimed at defining the modalities of this regulation, we analyze the available data concerning the state of fishery resources, particularly in the Northeast Atlantic. Indeed, this fishing zone has been at the center of recent debates related to the United Kingdom's exit from the European Union. The restoration of national sovereignty over British waters significantly mobilized fishermen during the Brexit vote in 2016. We present the consequences of this separation on the management of fish stocks in the Northeast Atlantic. A l'époque où la planète connaît sa sixième extinction de masse, la régulation de la pêche du poisson, source de protéine accessible sur l’ensemble du globe, est primordiale pour la gestion durable de cette ressource. Nous avons donc fait le point sur l’importance de cette filière à l’échelle mondiale, européenne et française. Après avoir présenté la construction et l’évolution des politiques européennes visant à définir les modalités de cette régulation, nous analysons les données disponibles concernant l’état des ressources piscicoles, en particulier dans l’Atlantique Nord-Est. En effet, cette zone de pêche est au coeur de débats récents liés à la sortie du Royaume-Uni de l’Union européenne. Le retour de la souveraineté nationale sur les eaux britanniques a massivement mobilisé les pêcheurs lors du vote du Brexit en 2016. Nous présentons les conséquences de cette scission sur la gestion des stocks de poisson dans l’Atlantique Nord-Est.